2015
DOI: 10.12738/estp.2015.3.2410
|View full text |Cite
|
Sign up to set email alerts
|

Structural Equation Modeling Towards Online Learning Readiness, Academic Motivations, and Perceived Learning

Abstract: The relationship between online learning readiness, academic motivations, and perceived learning was investigated via structural equation modeling in the research. The population of the research consisted of 750 students who studied using the online learning programs of Sakarya University. 420 of the students who volunteered for the research and filled the scales via the convenience sampling method constituted the research sample. The correlational research model was used in the research. The scales of online … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
28
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 40 publications
0
28
0
3
Order By: Relevance
“…Ya hemos mencionado que una razón para ello puede ser la multiplicidad de factores de los cuales depende. Una razón adicional a considerar es el hecho de que el rendimiento no necesariamente refleja el aprendizaje (Campbell & Cabrera, 2014), y hay bastante evidencia y fundamento teórico para sostener que la motivación tiene más que ver con el aprendizaje profundo que con el rendimiento (Espinar & Ortega, 2015;Horzum, Kaymak, & Gungoren, 2015;Pintrich, Marx, & Boyle, 1993). Por ello, tal vez sería más justo con el constructo CMC y las variables motivacionales en general, relacionarlos con medidas de aprendizaje efectivo y no meramente con rendimiento.…”
Section: Conclusionesunclassified
“…Ya hemos mencionado que una razón para ello puede ser la multiplicidad de factores de los cuales depende. Una razón adicional a considerar es el hecho de que el rendimiento no necesariamente refleja el aprendizaje (Campbell & Cabrera, 2014), y hay bastante evidencia y fundamento teórico para sostener que la motivación tiene más que ver con el aprendizaje profundo que con el rendimiento (Espinar & Ortega, 2015;Horzum, Kaymak, & Gungoren, 2015;Pintrich, Marx, & Boyle, 1993). Por ello, tal vez sería más justo con el constructo CMC y las variables motivacionales en general, relacionarlos con medidas de aprendizaje efectivo y no meramente con rendimiento.…”
Section: Conclusionesunclassified
“…One of the learners, for instance, stated in the interview, "As I am good at computer use, I did not have any difficulty understanding the concordancing program." This fact can be explained by learners' online learning readiness level, which was based on Horzum, Kaymak, and Güngören's (2015) study that found a positive relationship between learners' online learning readiness and their motivation. Thus, as the learners who received DDL instruction in the present study were willing and competent enough to work using a computer tool, they were found to be motivated as well.…”
Section: Discussionmentioning
confidence: 99%
“…• The online learning readiness level of learners is important and should be carefully raised by teachers, because the more time learners are engaged in corpora or related programs, the more motivated they feel (Horzum, Kaymak, & Güngören, 2015) and the more vocabulary they learn (Çelik & Keser, 2010).…”
Section: Implications For the Teaching/learning Situationmentioning
confidence: 99%
“…Teknoloji deneyimi daha fazla olan öğrencilerin eöğrenme algıları daha olumlu olmaktadır (Smart & Cappel, 2006) ve topluluk hisleri ne kadar güçlüyse, bununla ters orantılı olarak kendilerini izole hissetmektedirler (Song, Singleton, Hill & Koh, 2004). Çevrimiçi öğrenme hazır bulunuşluğu, öğrenciler arasındaki iletişim gibi durumlardan pozitif şekilde etkilemektedir (Horzum, Kaymak & Gungoren, 2015;Talsik, 2015). Öğrenenlerin çevrimiçi öğrenme ortamında birbirleri ile ve öğretim elemanı ile olan iletişimlerinin nasıl olduğunu anlamak gün geçtikçe önem kazanmaktadır.…”
unclassified
“…Öğrenme öz yönlendirmesi, öğrenenlerin başkalarından yardım alarak veya almayarak kişisel öğrenme ihtiyaçlarını teşhis etmeleri, hedef belirlemeleri, insan ve maddi kaynakları belirlemeleri, uygun öğrenme stratejilerini seçme ve uygulamaları ile öğrenme çıktılarını değerlendirmeleri şeklindeki eylemleri ile insiyatif aldıkları süreç olarak tanımlanabilir (Loyens, Magda & Rikers, 2008). Çevrimiçi öğrenme ortamlarında öğrenci doyumuna etki eden en önemli faktör motivasyondur (Kırmızı, 2015) ve çevrimiçi öğrenme hazır bulunuşluk düzeyleri akademik motivasyon tarafından tahmin edilebilmektedir (Horzum, Kaymak & Gungoren, 2015).…”
unclassified